L’absence de savoir conceptuel lors de démarches d’investigation scientifique mises en œuvre en classe : une crainte devenue réalité ? - Séverine Perron; Abdelkrim Hasni; Jean-Marie Boilevin (Recherches en Éducation)
Scientific inquiry are recommended both in institutional texts and in scientific documentation. In this research, we study the way in which French teachers articulate scientific investigation approaches (DIS) with conceptual knowledge in life and earth sciences. Our work is based on two constructs: scientific investigation approaches and conceptual knowledge. The method of data collection corresponding to the declared teaching practices is based on a mixed research of a descriptive nature. Our results highlight, among other things, the absence of learning objectives associated with conceptual knowledge when implementing BIDs in the classroom. It is mainly the skills and attitudes making up BIDs that are prioritized in a dissociated way from conceptualization.